ANALISIS PERSEPSI KARAKTER TOKOH TIGA SAUDARA DALAM DRAMA KOREA LITTLE WOMEN : STUDI DESKRIPTIF KUALITATIF PADA MAHASISWI UNIVERSITAS MUHAMMADIYAH CIREBON - Yusuf Sapari; Rizki Budhi Suhara; Salsabila Adzhani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2026)
This study aims to analyze the perceptions of female students at Universitas Muhammadiyah Cirebon towards the main characters in the Korean drama Little Women (2022). This drama, adapted from the classic novel by Louisa May Alcott, tells the story of three sisters who face moral and social dilemmas as they struggle against injustice and power structures. Using Miftah Toha's perception theory, which consists of three stages (stimulus, registration, and interpretation), this research examines how the narrative and cinematic elements of the drama shape audience perceptions of the central characters: Oh In-joo, Oh In-kyung, and Oh In-hye. The research adopts a qualitative descriptive approach, utilizing data collection techniques such as in-depth interviews, observations, and documentation from seven female student informants at Universitas Muhammadiyah Cirebon. The findings reveal that the audience's perceptions of these characters are influenced by the drama's narrative and cinematic quality, including its engaging storyline, strong character development, and visual elements such as lighting and costume that support the overall atmosphere. The character of Oh In-joo is perceived as pragmatic and realistic, Oh In-kyung as an idealistic figure fighting for justice, while Oh In-hye is viewed as a complex character with ambition and identity dilemmas. These findings contribute to the understanding of female representation in popular media and audience perceptions of characters within the context of Korean dramas.